Towards an understanding of the endogenous nature of identity in games - Katerina Bezrukova; John Smith (Rutgers University, Department of Economics, 2008)
We test the assumption that preferences are unchanged throughout a strategic game in the absence of feedback. To do so, we study the relationship between the strategic nature of a game and players' identification in social groups. We present evidence that the strategic nature of the game affects the strength of identity. We also show when the change in identity occurs and what causes this change. In our experiment, the subjects play one of two versions of the Prisoner's Dilemma game where the attractiveness of the uncooperative action is manipulated. We refer to the version with a relatively attractive uncooperative action as the Mean Game and the other as the Nice Game. We place each subject into one of two groups. Throughout the experimental procedure we measure identity, as standard in the psychology literature, in order to assess the extent to which subjects identify with their group. First, we find evidence of an interaction between the strategic nature of the game and the action selected in the game as affecting the identity of the subject. We find that in the Mean Game, there is little difference in the change in identification of those playing cooperatively against an ingroup member and those playing uncooperatively. However, in the Nice Game, those playing cooperatively against an ingroup member exhibit a significantly stronger change in identification than those playing uncooperatively. We find that the opposite is true for outgroup matches. Also, we show that the change in identity does not occur after initial inspection of the game but rather largely after the action choice has been made. Finally, we present evidence of an explanation of the effect: identity is enhanced by actions which are perceived to be less competitive and more cooperative.
Keywords: C7; C91; Z13; 330; identity; other-regarding preferences; endogenous preferences; endogenous identity; Spieltheorie; Nichtkooperatives Spiel; Gefangenendilemma; Theorie